2011
DOI: 10.1016/j.jvs.2011.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference survey in the management of asymptomatic carotid stenosis

Abstract: In this scenario, patients were split equally between medical and surgical treatment of asymptomatic carotid stenosis. This was identical to a recent poll of physicians. Tools for risk assessment and the results of the SPACE2, ACST2, and ACT1 trials would benefit patients and physicians making this important treatment decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Another issue when dealing with a population seeking information on the internet is that in spite of receiving information on the higher risk with CAS, some asymptomatic patients still prefer this compared to best medical therapy or surgery. 19 We had some similar experiences with patients arguing for the procedure without any strict indication.…”
Section: Discussionmentioning
confidence: 98%
“…Another issue when dealing with a population seeking information on the internet is that in spite of receiving information on the higher risk with CAS, some asymptomatic patients still prefer this compared to best medical therapy or surgery. 19 We had some similar experiences with patients arguing for the procedure without any strict indication.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 Given a recent survey demonstrating that a significant portion of patients still prefer CAS over CEA despite being quoted with a slightly higher periprocedural risks in comparison with CEA, one has to wonder whether patient preference is incorporated into the decision making in terms of carotid revascularization. 21 Recent studies have demonstrated a clear relationship between operator volume and improving outcomes after CAS. [22][23][24] Although there was an increase in the rate of CAS over time in our study, median hospital caseload only increased from 10 to 24 from 2001 to 2010 because of concomitant increase in the number of hospitals and likely operators performing CAS.…”
Section: Trends For Outcomes Of Cas and Cea 2001 To 2010mentioning
confidence: 99%
“…Respondents were not provided with a procedural risk of CEA, which has also changed over time and may vary between centres. Finally, patient preference was not taken into account; however, results from previous clinician and patient surveys in asymptomatic carotid disease have yielded similar preferences for management.…”
Section: Discussionmentioning
confidence: 99%